Out-of-plane behavior of innovative infill walls made of autoclaved aereated concrete (AAC) subjected to shake table tests - Giulivo, Marco; Borretti, Giovanbattista; Prota, Andrea; Menna, Costantino (Frontiers in Built Environment, 2023)
Introduction: Seismic damage affecting the non-structural components of buildings (such as infills) can significantly impact the expected economic losses over a structure’s service life. Recently, autoclaved aerated concrete (AAC) infills have gained attention in the construction industry due to their light weight, energy efficiency, and durability. Methods: This study investigates the out-of-plane behavior of an innovative AAC infill wall system by means of shake table tests. The wall system was made of low-density AAC units with innovative joints made from polyurethane resin and steel plates for connection to a structural frame. Shake table tests were carried out using artificial accelerograms based on ICBO-AC156, which can reproduce a wide range of interstory drift demands. The study is articulated in three stages: the mechanical characterization of the AAC infill wall, shake table tests, and seismic behavior analysis of the wall based on current code requirements. Results and Discussions: The results demonstrate the effectiveness of the innovative AAC infill wall system in resisting out-of-plane seismic loads, also considering different levels of seismic action, with base accelerations reaching up to 0.80 g.